Influência do capital social na saúde bucal de crianças e adolescentes - Knorst, Jessica Klöckner (2022)
Social capital, whose concept encompasses the positive consequences of sociability and social trust, has been highlighted as one of the main social determinants of health. Previous studies suggest that high social capital benefits oral health, however, some relevant issues surrounding this association have not been explored yet. Thus, the aim of this thesis was to evaluate the impact of social capital on the oral health of children and adolescents. For this, 4 articles were developed. The first systematically evaluated the association between social capital and oral health outcomes in children and adolescents; the second explored the direct and indirect pathways in which social capital in early childhood impacts dental caries and oral health-related quality of life (OHRQoL) in adolescence; the third evaluated the moderating effect of the sense of coherence (SOC) on the relationship between social capital and OHRQoL in schoolchildren; and the fourth evaluated the age period in which the OHRQoL is most affected by the social capital experienced in early childhood. For study 1, two calibrated reviewers performed the searches and selection of articles in relevant databases, and subsequent data extraction for narrative synthesis and meta-analysis. For studies 2, 3 and 4, a cohort was started in 2010 with 639 pre-schoolers (1-5 years old) in Santa Maria, Brazil. Individuals were reassessed in 2012, 2017 and 2020, totalling 10 years of follow-up (cohort retention rate of 67.1%). Community and individual social capital were assessed through the presence of formal institutions in the neighbourhood, individual social networks and social trust. Clinical and subjective measures of oral health included dental caries and OHRQoL. Demographic, socioeconomic, behavioural, and psychosocial (SOC) characteristics were also assessed. Data were analysed using Structural Equation Modelling for study 2 and Multilevel Poisson Regression Models for studies 3 and 4. The results of study 1 demonstrated that high social capital was associated with better clinical and subjective oral health outcomes, with the greatest impact of social capital at the community level. The findings of study 2 demonstrated that high community social capital in early childhood directly impacted lower occurrence of dental caries and better OHRQoL after 10 years. Community-level social capital also indirectly predicted lower occurrence of dental caries through psychosocial and behavioural pathways. Study 3 demonstrated that high SOC levels attenuated the negative impact of low individual social capital on OHRQoL. The results of study 4 showed that individual social capital in early childhood affected OHRQoL across cohort waves, while community-level social capital had a more long-term impact. Based on the studies, it is concluded that high levels of social capital positively impact normative and subjective oral health outcomes in children and adolescents, with the community level having a cumulative and greater impact. Furthermore, the relationship between social capital and oral health was especially influenced by psychosocial factors.